PROBIOTIC POTENCY OF LACTOBACILLUS SPP. ISOLATED FROM SUMBAWA MARE MILK - Sujaya, I Nengah; Utami Dwipayanti, I Made; Suariani, Ni Luh Putu; Widarini, Ni Putu; Ayu Nocianitri, Komang; Nursini, Ni Wayan (Jurnal Veteriner, 2008)
This research was deigned to elucidate the potency of Lactobacillus spp. isolated from sumbawa mare milk to be developed as a probiotic. Sixteen lacobacilli were screened based on their resitancy to a model of gastric juice at pH 2, 3, and 4, then followed by their resistncy to small intestional fluid model containing deoxycholic. Three lactobacilli i.e. Lactobacillus sp. SKA13, Lactobacillus rhamnosus SKG34 and Lactobacillus rhamnosus SKG49 were found to be resistentent to gastric juice at pH 3 and 4. However, there were no lactobacilli resisted to pH 2. Lactobacillus rhamnosus SKG34 and Lactobacillus rhamnosus SKG49 were able to reach the colon even after being expossed to a model of intestinal fluid containing 0,4 mM deoxycholate and pancreatine. Therefore, these isolates have a potency to be developed as probiotic lactobacilli. Nevertherless, these lactobcailli could probably transform cholic acid into secondary bile acids, which were not expected to be found in the probiotic, and this capability is not appropriate for probiotic. This character is worthly to be studied since it has never been reported in lactobacilli.
Keywords: Lactobacillus, Sumbawa mare milk, Probiotic